Nano-transethosomes: A Novel Tool for Drug Delivery through Skin - Bajaj, Kajal Jagdish; Parab, Bhagyashri Surendra; Shidhaye, Supriya Shrihari (Indian Journal of Pharmaceutical Education and Research, 2021)
Transdermal drug delivery has become a popular tool from last few years. It overcomes drawbacks which are encountered with the oral route. Though very few routes are as attractive as transdermal route, transport of drug through the skin is challenging. In order to overcome the challenges, researchers have found a system in which the drug is encapsulated into the vesicle and these vesicles can penetrate deeper into the skin to hit the target site. Hence, better skin penetration of bioactive agents can be achieved. Vesicular systems like liposomes, niosomes, ethosomes and Transferosomes tend to remain accumulated in the skin layers. Since Transethosomes have small particle size and can easily alter the shape of vesicle as compared with other vesicular systems; it can penetrate through the layers of skin. Hence, the drug encapsulated into Transethosomes can easily reach the target site. Transethosomes consist of ethanol, phospholipids along with an edge activator. Ethanol and edge activator help to enhance skin permeation of Transethosomes. Since it is a non-invasive technique, it improves patient compliance. It also increases drug entrapment efficiency. These vesicles can accommodate different variety of drugs such as anticancer, corticosteroids, proteins and peptides, analgesics.
Keywords: Transdermal delivery system; Transethosomes; Vesicles; Skin permeation; Non-invasive; Entrapment efficiency